Impact of the COVID-19 pandemic on the management of dental pain and odontogenic infections in pediatric patients - Nádia Carolina Teixeira Marques (Journal of Dental Research and Review, 2022)
Objective: This study aimed to compare the number of procedures for dental pain relief and odontogenic infection control performed annually in pediatric patients before and during the pandemic to date. Methods: The longitudinal association between the number of procedures to treat pediatric urgent dental emergencies from the previous (2017–2019) to the pandemic (2020) period was evaluated by a negative binomial regression in the form of incidence rate ratio with 95% confidence interval. Results: This study showed a significant decrease in the number of pulp capping, pulpotomy, access to dental pulp and medication, endodontic medication with/without biomechanical root canal preparation, abscess drainage, and extraction of primary or permanent teeth, performed in patients up to 12 years old from the previous to the pandemic period. Conclusions: Therefore, the COVID-19 pandemic has adversely impacted on the number of procedures for dental pain relief and odontogenic infection control performed in pediatric patients.